Eye and neck proprioceptive messages contribute to the spatial coding of retinal input in visually oriented activities - Roll, R; Velay, J L; Roll, J P (Experimental brain research, 1991)
The egocentric localization of objects in extrapersonal space requires that the retinal and extraretinal signals specifying the gaze direction be simultaneously processed. The question as to whether the extraretinal signal is of central or peripheral origin is still a matter of controversy, however. Three experiments were carried out to investigate the following hypotheses: 1) that the proprioceptive feedback originating in eye and neck muscles might provide the CNS with some indication about the gaze direction; and 2) that the retinal and proprioceptive extraretinal inputs might be jointly processed depending on whether they are of monocular or binocular origin. Application of low amplitude mechanical vibrations to either the extraocular or neck muscles (or both) of a subject looking monocularly at a small luminous target in darkness resulted in an illusory movement of the target, the direction of which depended on which muscle was stimulated. A slow upward target displacement occurred on vibrating the eye inferior rectus or the neck sterno-cleido-mastoidus muscles, whereas a downward shift was induced when the dorsal neck muscles (trapezius and splenius) were vibrated. The extent of the perceptual effects reported by subjects was measured in an open-loop pointing task in which they were asked to point at the perceived position of the target. These results extend to visually-oriented behavior the role of extraocular and neck proprioceptive inputs previously described in the case of postural regulation, since they clearly show that these messages contribute to specifying the gaze direction. This suggests that the extraretinal signal might include a proprioceptive component.